1961
DOI: 10.2118/33-pa
|View full text |Cite
|
Sign up to set email alerts
|

Multiple Liquid Phases in a Natural-Gas System

Abstract: During a recent phase study of a natural gas, two stable equilibrium liquid phases were observed at temperatures below –200F and pressures above 200 psi. This paper reviews the published literature on the occurrence of multiple equilibrium liquid phases and presents analytical data for the vapor and two equilibrium liquid phases of the liquefied natural gas at five experimental conditions. In addition, data for 30 conditions of two-phase equilibria are included. Introduc… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1

Citation Types

0
2
0

Year Published

1983
1983
2010
2010

Publication Types

Select...
4

Relationship

0
4

Authors

Journals

citations
Cited by 4 publications
(2 citation statements)
references
References 0 publications
0
2
0
Order By: Relevance
“…Finally, to investigate whether the PC-SAFT EoS provides good accuracy for multicomponent systems with only binary information, this model was applied to the modeling of the vapor-liquid equilibrium data for 43 multicomponent mixtures containing hydrocarbon (methane, ethane, propane, n-pentane, n-heptane, and n-decane) and nonhydrocarbon (nitrogen, carbon dioxide, and hydrogen sulfide) components, studied experimentally by Yarborough, 36 and the three-phase vapor-liquid-liquid equilibrium data of a natural gas system rich in nitrogen, reported by Stroud et al 7 The results of the modeling obtained for these systems indicate that the PC-SAFT EoS can be used with confidence to predict the phase behavior of multicomponent systems by using interaction parameters obtained only from experimental binary vapor-liquid equilibrium data.…”
Section: Resultsmentioning
confidence: 99%
See 1 more Smart Citation
“…Finally, to investigate whether the PC-SAFT EoS provides good accuracy for multicomponent systems with only binary information, this model was applied to the modeling of the vapor-liquid equilibrium data for 43 multicomponent mixtures containing hydrocarbon (methane, ethane, propane, n-pentane, n-heptane, and n-decane) and nonhydrocarbon (nitrogen, carbon dioxide, and hydrogen sulfide) components, studied experimentally by Yarborough, 36 and the three-phase vapor-liquid-liquid equilibrium data of a natural gas system rich in nitrogen, reported by Stroud et al 7 The results of the modeling obtained for these systems indicate that the PC-SAFT EoS can be used with confidence to predict the phase behavior of multicomponent systems by using interaction parameters obtained only from experimental binary vapor-liquid equilibrium data.…”
Section: Resultsmentioning
confidence: 99%
“…1,2 Experimental VLLE data have been reported for the systems nitrogen + ethane, 3,4 nitrogen + propane, 4 and nitrogen + methane + ethane, [3][4][5] including an observation of four fluid phases (one vapor phase and three liquid phases) at T ) 112.2 K and p ) 1.403 MPa for this ternary system. 6 Stroud et al 7 also reported VLLE data for a nitrogen-rich natural gas system from T ) (116 to 130) K and pressures up to 3.447 MPa. Subsequently, data of the two coexisting liquid phases in binary and ternary mixtures of nitrogen with n-alkanes have been published by Kohn and co-workers.…”
Section: Introductionmentioning
confidence: 98%